Roundabouts as Safe and Modern Solutions in Transport Networks and Systems 15th Scientific and Technical Conference "Transport Systems. Theory and Practice 2018", Katowice, Poland, September 17-19, 2018, Selected Papers - Macioszek, Elżbieta; Akçelik, Rahmi; Sierpiński, Grzegorz (Lecture Notes in Networks and Systems,, 2019)
This book offers a collection of guidelines that will be particularly useful to those making decisions concerning roundabouts as safe and modern solutions in transport networks and systems. The decision-making support systems described here will interest those who face the challenge of finding solutions to problems concerning modern transport systems on a daily basis. Consequently, the book is chiefly intended for local authorities involved in planning and preparing development strategies for specific transport-related issues (in both urban and regional contexts), as well as for representatives of business and industry who are directly engaged in the implementation of traffic engineering solutions. The guidelines provided in the respective chapters help to address the given problem soundly, and to simplify the selection of an appropriate strategy. The topics covered include traffic conditions and the performance of single-lane, two-lane and turboroundabouts, road traffic safety analysis, analysis of road traffic safety improvements, surrogate safety measures at roundabouts, analysis of pedestrian behavior at pedestrian crossings with public transport vehicles, methods for assessing vehicle motion trajectory at single-lane roundabouts using visual techniques, making compact two-lane roundabouts effective for vulnerable road users, concepts for wireless electric vehicle charging near roundabouts, work zones, and temporary traffic control at roundabouts. Since the book also considers new approaches to theoretical models (including modeling roundabout capacity, models of critical gaps and follow-up headways for turbo roundabouts, and estimating roundabout delay while taking into account pedestrian impact), it will also appeal to researchers and scientists studying these problems. The book gathers selected papers presented at the 15th Scientific and Technical Conference "Transport Systems. Theory andPractice", organized by the Department of Transport Systems and Traffic Engineering, Silesian University of Technology in Katowice, Poland on September 17-19, 2018.